Studies on land alienation perspective under MADA administration in Perlis and Jitra / Muhammad Firdaus Hussin - Hussin, Muhammad Firdaus (2019)
Paddy is one of major industries in Malaysia. In order to manage and sustaining the production of paddy in this country, an organization with a systematic planning must be established. Hence, under the Ministry of Agriculture (MoA), Muda Agriculture Development Authority (MADA) has been established with the main aim to lead the country’s paddy industry and to improve the socio-economic of farmers in Muda area. By the record in 2017, the area of paddy cultivation is about 100,685 hectares. With the large area under MADA, it might have problem to manage and to look after especially on land administration. Thus, this aim of this paper is to study on paddy field land alienation status under MADA administration. This study involving two aspects which are Social Science and Science Technology. Also, this study was covered on two Wilayah under MADA administration which are Perlis and Jitra involving 14 Pertubuhan Peladang Kawasan (PPK). To smoothen the progress of this study, there are few government organizations that involved such as Department of Survey and Mapping Malaysia (DSMM), land office and others. The data collected for this study were divided into two parts which are primary and secondary. The primary data comes from questionnaire and the secondary comes from land title certificate. The data were processed by using SPSS software, ArcGIS and also Microsoft Excel. From the processed data, a database were developed with the aid of using ArcGIS software to produce a map showing the status of paddy field land alienation under MADA administration and its analysis. The result and analysis from this study can be used to help MADA in making decisions and updating their database regarding land alienation status.